Analisis Kebutuhan Masyarakat Dalam Kebersihan Lingkungan Desa Namobintang - Ibnu Hajar; Sardi Pranata; Putie Nurul Aina; Nur Hasanah Yugid Siregar; Riskyana Br Damanik; Khofifah Tanjung; Della RCP Sarumapae; Amanda Granesia Br Ginting; Ruth Cyntya Damayanti Damanik; Valentina Sinurat; Iwan Saktiawan Sinamo; Gerard Dika Purba; Angel Charonita Br Bangun (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2026)
Environmental cleanliness is an important factor in creating a healthy, comfortable, and high-quality community life. However, in reality, there are still various environmental cleanliness problems influenced by community behavior, level of awareness, and the availability of sanitation facilities and infrastructure. This study aims to analyze community needs in maintaining environmental cleanliness in Namobintang Village, including the condition of environmental cleanliness, factors influencing community awareness and participation, the role of village government and community leaders, as well as the availability of sanitation facilities and infrastructure. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results show that the condition of environmental cleanliness in Namobintang Village is still not optimal. This can be seen from improper household waste management, poorly maintained drainage systems, and low community participation in cleanliness activities. The factors influencing these conditions include the level of community awareness, habits and culture, level of education, and limited sanitation facilities. In addition, the role of the village government and community leaders in increasing awareness and participation is considered not yet optimal, both in terms of socialization and provision of sanitation facilities. Thus, it can be concluded that environmental cleanliness in Namobintang Village is influenced by community behavior, availability of facilities and infrastructure, and the role of the village government. Therefore, more targeted and sustainable efforts are needed through increasing community awareness, providing adequate sanitation facilities, and strengthening the role of the village government and community leaders in creating a clean and healthy environment.